Javanese Mosaic: Three Polish representations of Java from the second half of the 19th century. Issue 147 (4th May 2022) - Ewertowski, Tomasz
ABSTRACT: This article attempts to analyse some images of Java in Polish travel writings from the second half of the 19th century in a comparative framework, and linking the various aspects of representations of the island with the respective travellers' background, social and intellectual trends of the epoch, and literary conventions. This approach is based on concepts of imagology, habitus and comparative reading. The travelogues by three Polish authors are analysed here: aristocrat, lawyer and politician Adam Sierakowski (1846–1912), soldier Henryk Sienkiewicz (1852–1936, a relative of a famous writer by the same name), and an apostolic delegate for the East Indies Władysław Michał Zaleski (1852–1925). Polish travel accounts are juxtaposed with texts written by English, American, Russian, and Javanese travellers: Charles Kinloch (1810–1893), Eliza Ruhamah Scidmore (1856–1928), V. Tatarinov (c.1860), Nikolai Miklouho-Maclay (1846–1888), and Radèn Mas Arya Candranegara V alias Purwalelana (1837–1885). The examples show that although some descriptive aspects of Java may be linked to national identity, far more fruitful would be a detailed examination of texts and contexts through a comparative analysis.